Konstruksi Realitas Cover Majalah Tempo (Studi Semiotika Gambar Jokowi Bersiluet Pinokio) - Laurensia Retno Hariatiningsih; Irwanto Irwanto Irwanto (J-IKA : Jurnal Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas BSI Bandung, 2021)
In September 2019 Indonesia was busy discussing the revision of the Corruption Eradication Commission Law which was passed, in this condition Tempo magazine depicts the symbol of President Jokowi with the silhouette of Pinocchio on the cover of the 16-22 September 2019 edition of Tempo magazine. The purpose of this study describes the meaning of the signs and symbols is included in the cover of the Tempo magazine edition dated 16-22 September 2019. Apart from that, he also wants to reveal the meaning contained in the cover of the Tempo magazine. This study uses a constructivist paradigm, with a descriptive qualitative research approach using Charles Sander Pierce's triadic semiotic analysis model. The results showed that the sign of a man dressed in white with wrinkles on the forehead and pouting lips, this shows the problems that occur in Indonesia so that the president is responsible for handling corruption cases. The silhouette of President Jokowi with a long nose resembling Pinocchio here is a depiction of Pinocchio's character. Here, Tempo tries to be critical about events in the community, and with this picture the people have their own perceptions of the current situation.  Keywords: Reality Construction, Magazine Cover, Triadic Model SemioticsCharles Sander Pierce.